Respuesta :

assuming you mean [tex](5x)^ \frac{-5}{4} [/tex]

remember
[tex]x^{-m}= \frac{1}{x^m} [/tex] and
[tex]x^ \frac{m}{n}= \sqrt[n]{x^m} [/tex]

combining we get
[tex]x^ \frac{-m}{n}= \frac{1}{x^\frac{m}{n}} = \frac{1}{ \sqrt[n]{x^m} } [/tex]
so

[tex](5x)^ \frac{-5}{6}= \frac{1}{(5x)^\frac{5}{4}} = \frac{1}{ \sqrt[4]{(5x)^5} } =\frac{1}{ 5x\sqrt[4]{5x} } [/tex]


[tex]\bf a^{\frac{{ n}}{{ m}}} \implies \sqrt[{ m}]{a^{ n}} \qquad \qquad \sqrt[{ m}]{a^{ n}}\implies a^{\frac{{ n}}{{ m}}} \\\quad \\a^{-\frac{{ n}}{{ m}}} = \cfrac{1}{a^{\frac{{ n}}{{ m}}}} \implies \cfrac{1}{\sqrt[{ m}]{a^{ n}}}\qquad\qquad \cfrac{1}{\sqrt[{ m}]{a^{ n}}}= \cfrac{1}{a^{\frac{{ n}}{{ m}}}}\implies a^{-\frac{{ n}}{{ m}}} \\\\ -----------------------------\\\\[/tex]

[tex]\bf thus \\\\ (5x)^{-\frac{5}{4}}\implies \cfrac{1}{(5x)^{\frac{5}{4}}}\implies \cfrac{1}{\sqrt[4]{(5x)^5}}\implies \cfrac{1}{\sqrt[4]{5^5x^5}} \\\\ \cfrac{1}{5x\sqrt[4]{5x}}[/tex]